2009
DOI: 10.1128/jcm.00469-08
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis of Rubella Virus Strains from an Outbreak in Madrid, Spain, from 2004 to 2005

Abstract: Rubella virus (RUBV) usually causes a mild exanthematous disease that is frequently accompanied by adenopathy and occasionally by arthralgia. Complications of this infection are rare and include encephalopathy and thrombocytopenia. However, the most severe consequence of this virus is its teratogenicity. It can cause congenital rubella syndrome (CRS) when it occurs in pregnant women, particularly during the first trimester of pregnancy (10).The direct detection of RUBV RNA in clinical specimens, in addition to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
0
16
0
2
Order By: Relevance
“…WHO Laboratory Network for measles and rubella viruses surveillance reported the global distribution of RUBV genotypes, showing that in Europe genotype 1E and 1G are predominant [WHO, 2006; Hubschen et al, 2007]. More recently, the circulation of genotype 1j was documented in Spain, possibly introduced by persons from Latin America [Martinez‐Torres et al, 2009]. Genotype 2B is autochthonous in the Far East, namely Japan and Korea, and in South Africa, although it is now considered an imported European genotype [Jin and Thomas, 2007; Novo et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…WHO Laboratory Network for measles and rubella viruses surveillance reported the global distribution of RUBV genotypes, showing that in Europe genotype 1E and 1G are predominant [WHO, 2006; Hubschen et al, 2007]. More recently, the circulation of genotype 1j was documented in Spain, possibly introduced by persons from Latin America [Martinez‐Torres et al, 2009]. Genotype 2B is autochthonous in the Far East, namely Japan and Korea, and in South Africa, although it is now considered an imported European genotype [Jin and Thomas, 2007; Novo et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
“…The latter assay which is based on amplification of fragments of 289 base pairs (pb) of the rubella virus glycoprotein E1 gene, of 229 pb of the measles virus nucleoprotein gene and of 94 pb of the PVHB19 protein VP1 gene, has shown excellent sensitivity for the detection of measles and PVHB19, with a lower sensitivity for rubella. It has recently been confirmed that the addition of betaine, a reducing agent, to the amplification reaction, significantly improves the sensitivity of assays used for detecting the rubella virus genome [12].…”
Section: Direct Diagnosis: Nucleic Acid Detectionmentioning
confidence: 98%
“…En el virus de la rubéola el genotipado se basa en una secuencia de 739 nt (del nt 8731 al nt 9469) de la región codificante del gen E1 13 . Para describir un nuevo genotipo se necesita la secuencia completa de la región del genoma que codifica las proteínas estructurales (3192 nt) de dos cepas de referencia para cada genotipo.…”
Section: Técnicas De Genotipadounclassified